Charlie's angels, full throttle [videorecording (DVD)] - Shearmur, Edward (Columbia TriStar Home Entertainment, 2003)
Summoned by their boss, the angels are given their latest assignment. A pair of rings have been stolen and need to be recovered. The rings have been coded with special information that can be used to access a list of every person in the FBI's Witness Protection Program. While searching for the culprits, they encounter Madison Lee, one of Charlie's former agents who decided that the wrong side of the law pays better, and Seamus, who once dated Dylan and wants revenge for her decision to turn him over to the police.